2012
DOI: 10.1111/j.1708-8208.2012.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dental Implant Diameter on Fatigue Performance. Part II: Failure Analysis

Abstract: The results of this study indicate that proper implant design is crucial to ensure long-term fatigue performance for dental implants. The combination of sharp notches (thread) and narrow metal cross section is quite deleterious for fatigue resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 10 publications
7
37
0
2
Order By: Relevance
“…In 3.3 mm implants, 52% of the fractured implants were fractured at the implants second thread and 48% were fracture at the implants third thread. This result is in agreement with our case [17]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In 3.3 mm implants, 52% of the fractured implants were fractured at the implants second thread and 48% were fracture at the implants third thread. This result is in agreement with our case [17]. …”
Section: Discussionsupporting
confidence: 94%
“…Excessive overloading produces increase in number of dislocation, which, by virtue of their interactions and stress field, gives rise to higher state of internal stresses and consequently leads to fatigue fracture. Shemtov-Yona et al [19] also proposed that the nontypical fatigue behavior observed for 3.3 mm implant diameter is probably the result of stress concentrations generated along the structure's surface.…”
Section: Sem Analysis Of Fractured Implant Fragmentmentioning
confidence: 99%
“…Failures chiefly involved the integrity of the abutment's screw in external hexagon connections, which is expected, considering that the abutment is mainly stabilized by its torqued screw eventually challenged by oblique loading . In contrast, the high stress concentration at the cervical thin area of the IH connection during loading surpassed the yield strength of the NDIs, leading to the least desirable complication, implant fracture in lieu of abutments or their screws, which remained intact in this group . Regarding IC and IC‐M, failures were restricted to abutments and screw system; no implant fracture was observed.…”
Section: Discussionmentioning
confidence: 80%
“…8,[15][16] The cause(s) for fatigue crack initiation was first shown to be related to implant design that includes significant stress concentrators. 15,[17][18] Accelerated fatigue failure was also observed for implants that were ϳ cyclically loaded in a saliva-like environment, 19 indicating the potentially adverse effects of the in-vitro atmosphere. Moreover, the surface roughening procedure, aimed at promoting osseointegration 20 was also evaluated as a potentially damaging factor to the mechanical performance and reliability of the implants.…”
Section: Introductionmentioning
confidence: 99%